Phytochemical Screening and Antibacterial Activity of Syzygium cumini (L.) (Myrtaceae) Leaves Extracts - Tambe, Bhavana Dnyandeo; Pedhekar, Pratiksha; Harshali, Pardeshi (Asian Journal of Pharmaceutical Research and Development, 2021)
The phytochemical analysis of the medicinal plants are important and have commercial interest in both research institutes and pharmaceutical companies for the manufacturing of the new drugs for treatment of various diseases. The present study was aimed to investigate the preliminary phytochemical screening of the seeds of Syzygium cumini belonging to family Myrtaceae. The results revealed the presence of medicinally important phytochemical constituents in the ethyl acetate and methanol extracts of Syzygium cumini seeds and it justifies their use in the traditional medicines for the treatment of different diseases. Phytochemical investigation was carried out on the crude methanol and aqueous extracts of the leaves of Syzygium cumini (L.) The antimicrobial activity of the extract was tested against standard strains and clinical isolates of some bacteria using the disc diffusion method. Preliminary phytochemical studies revealed the presence of flavonoids, alkaloids, glycosides, steroids, phenols, saponins, terpenoid, cardiac glycosides and tannins as the chemical class present in the extracts. The extracts showed inhibitory activity against clinical isolates of the gram negative bacteria such as Salmonella enteritidis, Salmonella typhi, Salmonella typhi A, Salmonella paratyphi A, Salmonella paratyphi B, Pseudomonas aeruginosa and Escherichia coli. Gram positive bacteria are Bacillus subtilis, and Staphylococcus aureus. The results showed that the methanol extracts was more potent than the aqueous extracts.